Stability of social behavior in captive American Flamingos (Phoenicopterus ruber): A quantitative case study. Issue 4 (17th April 2015) - Hughes, Austin L.
<x xml:space="preserve">Abstract</x> Over a three‐year period a captive American flamingo (Phoenicopterus ruber) group showed recurring seasonal changes in the pattern of agonistic behavior. In spite of seasonal changes in the rates of agonistic behavior, dominance relations were generally stable across seasons. Males had significantly higher dominance status than females, and birds in long‐term male–female pair bonds had significantly higher dominance than others. Unresolved agonistic encounters (URI), those with no clear winner or loser, were frequently observed; and their pattern of occurrence changed over the course of the year. URI were most frequent on the breeding "island" during the breeding season, and at the feeder in the post‐breeding season. Thus, the frequency of URI reliably tracked seasonal changes regarding the resources most in contention; and, the extent of an individual's involvement in URI was indicative of privileged access to resources over which competition occurred. Zoo Biol. 34:305–313, 2015. © 2015 Wiley Periodicals Inc.